2015
DOI: 10.1007/s10554-015-0685-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic consequences of non-cardiac incidental findings detected on cardiovascular computed tomography performed prior to transcatheter aortic valve implantation (TAVI)

Abstract: Transcatheter aortic valve implantation (TAVI) is an effective treatment option for patients with severe degenerative aortic valve stenosis who are high risk for conventional surgery. Computed tomography (CT) performed prior to TAVI can detect pathologies that could influence outcomes following the procedure, however the incidence, cost, and clinical impact of incidental findings has not previously been investigated. 279 patients underwent CT; 188 subsequently had TAVI and 91 were declined. Incidental findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…There is no doubt that extracardiac findings are common in cardiac CT if the examiner looks beyond the heart, reinforcing what has been reported previously for non-contrast-enhanced low-resolution studies such as CTAC 13,18 or coronary artery calcium scoring, 19 and contrast-enhanced studies such as cardiac CT angiography, 20 or cardiovascular CT prior to TAVI, 21 or pulmonary vein isolation. 22 The key question is whether the recognition of these non-cardiac findings translates into patient benefit or might even harm the patient.…”
Section: See Related Article Pp 1574-1583supporting
confidence: 75%
See 1 more Smart Citation
“…There is no doubt that extracardiac findings are common in cardiac CT if the examiner looks beyond the heart, reinforcing what has been reported previously for non-contrast-enhanced low-resolution studies such as CTAC 13,18 or coronary artery calcium scoring, 19 and contrast-enhanced studies such as cardiac CT angiography, 20 or cardiovascular CT prior to TAVI, 21 or pulmonary vein isolation. 22 The key question is whether the recognition of these non-cardiac findings translates into patient benefit or might even harm the patient.…”
Section: See Related Article Pp 1574-1583supporting
confidence: 75%
“…However, in multivariate analysis, outcomes after TAVI were not influenced by any category of incidental finding. 21 Additionally, a retrospective observational study including 414 patients undergoing CT prior to transcatheter aortic valve replacement detected a potentially malignant incidental finding in 19% of patients-with no impact on 2-year survival. 23 Although these patient cohorts differ significantly from those undergoing MPI by SPECT taking into account the high mortality rate of patients with severe aortic stenosis.…”
Section: See Related Article Pp 1574-1583mentioning
confidence: 99%
“…Lindsay et al in a recent study demonstrated that incidental findings in pre-TAVI CT are common, and do not independently identify patients with poor outcomes after TAVI procedure [11]. Detection of incidental findings on CT should not necessarily influence or delay the decision to perform TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…MDCT images are acquired through the chest, abdomen, and pelvis with a large imaging field of view, and potential incidental non-cardiac findings (INCFs) can be detected. The prior unknown abnormalities that are identified on MDCT without previous suspicion of disease and unrelated to the indications of the examination are referred to as incidental findings [11]. Presence of INCFs at the time of MDCT poses important challenges and management issues.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, during CT aortography, images are acquired throughout the thorax and abdomen, and potentially significant incidental findings can be found. Until today patients candidates to TAVR tend to be elderly and it has been shown a very high overall incidence of incidental pathological findings in this population (more than 50%) and in 18.1% of cases a clinical signification has been documented[99]. …”
Section: Multislice Computed Tomographymentioning
confidence: 99%